Characterization of Cellulose Microfibers Isolated from Rubberwood (Hevea brasiliensis) - Junidah, Lamaming; Nurul Hasni, Sharudin; Rokiah, Hashim; Othman, Sulaiman (INSIGHT - Indonesian Society for Knowledge and Human Development, 2016)
— Cellulose microfibers were isolated by chemical treatment followed by acid hydrolysis using sulphuric acid. The chemical compositions for extractive, holocellulose, cellulose and lignin were determined. The functional group of raw particles and cellulose microfibers of rubberwood were determined using fourier transform infrared spectroscopy (FT-IR). Morphological studies were viewed using Scanning Electron Microscopy (SEM) to investigate physical changes of the fibers after acid hydrolysis. The results show that cellulose content was increased to 63 % from 52 % after hydrolysis was conducted to the raw particles. Particle size distribution of cellulose microfibers falls in the range of below 100 µm. The removal of lignin and other extractives during chemical and acid hydrolysis can be seen by the absence of certain band in the FTIR spectra. The individualization of the fibers can be seen after hydrolysis with sulphuric acid. The removal of the surface impurities along with defibrillation were also shown in the cellulose microfibers.